Precursors of pancreatic cancer - Frič, Přemysl; Škrha, Jan; Šedo, Aleksi; Bušek, Petr; Laclav, Martin; Bunganič, Bohuš; Zavoral, Miroslav (European journal of gastroenterology & hepatology, 2017)
Pancreatic cancer (PC) behaves very differently in comparison with other malignancies. Its incidence has been increasing continuously; mortality has not decreased, the diagnosis is frequently late, radical surgery is performed only in 15-20% of patients, and chemotherapy is only palliative. PC occurs in three different forms. Sporadic PC accounts for 90% of all PCs. Its most frequent form is the pancreatic ductal adenocarcinoma. The remaining 10% constitute two minority groups: familial PC (7%) and PC as a manifestation of a genetic cancer syndrome (3%). PCs are preceded by a precancerous lesion (precursor). At present, six different precursors are known. They have different histomorphological characteristics and malignant potential. The recognition and correct interpretation of individual precursors influences adequate clinical decision-making. The publication surveys the present knowledge of individual precursors and their role in the early pancreatic carcinogenesis.
Keywords: duktální karcinom slinivky břišní; signální transdukce; Signal Transduction; Carcinoma, Pancreatic Ductal; regulace genové exprese u nádorů; nádory slinivky břišní; prekancerózy; Epigenesis, Genetic; Humans; lidé středního věku; Biomarkers, Tumor; Female; rizikové faktory; Aged; Early Detection of Cancer; senioři; lidé; zvířata; nádorová transformace buněk; časná detekce nádoru; nádorové biomarkery; epigeneze genetická; ženské pohlaví; Precancerous Conditions; Male; Pancreatic Neoplasms; Middle Aged; prognóza; Cell Transformation, Neoplastic; Animals; mužské pohlaví; Gene Expression Regulation, Neoplastic; Prognosis; Risk Factors